Unsur seksualiti dan materialisme dalam karya Bernard Chauly dan Rafidah Abdullah / Nurul Atiqah Ibrahim - Nurul Atiqah , Ibrahim (2018)
The study of Sexuality Elements and Materialism in Bernard Chauly and Rafidah Abdullah discussed the modernization that led to the occurrence of cultural diffusion that occurred from outside countries affecting Malay culture and society in Malaysia. This study describes in detail the narrative of the film by Bernard Chauly and Rafidah Abdullah. Through the narrative, the researchers then discussed the element of sexuality and materialism influencing modern Malay society in Malaysia. In addition to referring to the concepts chosen and from previous scholarly studies, this study is also linked to the reality of the Malay community today. Qualitative study methods were used in this study such as library research and interviews. The findings show that as the era of modernization develops, the emergence of external cultural elements into Malay society in Malaysia is not only evolving through the medium of film even from the reality of the life of the society itself. Some cases that occur in Malaysia involve Malays in relation to the relevant external cultural elements are also discussed in this study. In conclusion, modernization has given way to diffusion of various aspects such as film and lifestyle for a society.